2007
DOI: 10.1002/jsfa.3050
|View full text |Cite
|
Sign up to set email alerts
|

Properties of refrigerated ground beef treated with potassium lactate and sodium diacetate

Abstract: BACKGROUND: Ground meat is product that perishes easily and therefore various preservatives are applied to prolong its shelf life. The aim of this study was to investigate the effect of potassium lactate and sodium diacetate (Protec K-DI preparation) on general proteolytic activity, protein degradation, texture, colour and water-holding capacity of vacuum-packaged ground beef.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Contrary to this, Fik et al. (2008) reported that the total activity of proteolytic enzymes and the rate of hydrolysis of protein substances were significantly higher in the samples stored with the addition of preservative (PL and sodium diacetate) than those in the control sample. Proteolytic degradation is reduced thanks to the antioxidant properties of nitrate.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Contrary to this, Fik et al. (2008) reported that the total activity of proteolytic enzymes and the rate of hydrolysis of protein substances were significantly higher in the samples stored with the addition of preservative (PL and sodium diacetate) than those in the control sample. Proteolytic degradation is reduced thanks to the antioxidant properties of nitrate.…”
Section: Resultsmentioning
confidence: 86%
“…Fik et al. (2008) found that the addition of PL and sodium diacetate caused an increase in the relative content of polypeptides (100 g/L TCA precipitable fraction) and a decrease in the amounts of some amino acids. Factors such as raw material properties (pH, aw, and enzymes), materials used in curing and usage rates, curing time, drying temperatures, cemening, and microbial flora affect the proteolytic breakdowns that occur during pastırma production (Erdemir, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PL is a potential alternative compound which may be used for this aim. In previous studies PL is used for various purposes such as antimicrobial (Kim et al 2010) and antioxidant (Mancini et al 2010) activities, colour (Brewer et al 1995Kim et al 2009;2010), tenderness and texture (Fulladosa et al 2009) improvement, increased cook yields (Papadopoulos et al 1991), flavour development, proteolytic effect (Fik et al 2008) and also improvement of shelf life (Brewer et al 1995;Kim et al 2009;2010;Choi et al 2014) of meat and meat products. However, the effects of PL on free amino acids and meat ultrastructure are not well known.…”
Section: Introductionmentioning
confidence: 99%